Integrating Local Wisdom Into Sustainable Entrepreneurship Models: A Conceptual Approach For Climate Action - Lalu Agustino; Muhammad Nawawi; Muhammad Ridhoni; Ridzki Dian Rithauddin (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Climate change is a critical global challenge that demands innovative, cross-sectoral solutions. Sustainable entrepreneurship integrates social, environmental, and economic dimensions, fostering long-term positive impacts. However, many business models overlook the strategic potential of local wisdom to enhance sustainability. This study addresses this gap by developing a conceptual framework that incorporates local values into sustainable entrepreneurship, offering a novel approach to climate change mitigation. Using a conceptual methodology based on extensive literature analysis, the framework integrates the Triple Bottom Line (TBL)—People, Planet, Profit—and the Business Model Canvas (BMC) while embedding local wisdom, such as ecological harmony, community-based resource management, and cultural preservation. These elements are mapped onto BMC components like Value Proposition, Revenue Streams, and Key Activities, providing actionable strategies to align business operations with local traditions and global sustainability goals. This framework enhances community resilience and directly supports climate action while promoting sustainability in sectors like agribusiness and tourism. By bridging traditional knowledge systems and modern practices, it offers a practical and scalable solution for advancing global sustainability efforts. Further empirical validation is recommended to assess its feasibility across diverse contexts.